Gamifying the teaching of Dentistry: Seriously playing. - Saravia-Rojas, Miguel A. (2022)
The teaching of dentistry changed. The effects of the pandemic, the virtualization of contents, and students belonging to Generation Z, demand for student-centered teaching where the classic teacher-centered learning is transformed into a student-centered education approach using didactic strategies like gamification. In this article, an experience carried out among fifth semester dental students is shared, using the resources of gamification to generate a meaningful teaching, leaving aside the master classes, and migrating to more efficient and effective student-centered learning models that generate a real commitment and motivation. Likewise, the perception of the students about the activity is shared.